Neuromuscular Adaptations to Different Modes of Combined Strength and Endurance Training - Eklund, D.; Pulverenti, T.; Bankers, S.; Avela, J.; Newton, R.; Schumann, M.; Häkkinen, K. (International Journal of Sports Medicine, 2015)
The present study investigated neuromuscular adaptations between same-session combined strength and endurance training with 2 loading orders and different day combined training over 24 weeks. 56 subjects were divided into different day (DD) combined strength and endurance training (4–6 d·wk-1) and same-session combined training: endurance preceding strength (E+S) or vice versa (S+E) (2–3 d·wk-1). Dynamic and isometric strength, EMG, voluntary activation, muscle cross-sectional area and endurance performance were measured. All groups increased dynamic one-repetition maximum (p<0.001; DD 13±7%, E+S 12±9% and S+E 17±12%) and isometric force (p<0.05–0.01), muscle cross-sectional area (p<0.001) and maximal power output during cycling (p<0.001). DD and S+E increased voluntary activation during training (p<0.05–0.01). In E+S no increase in voluntary activation was detected after 12 or 24 weeks. E+S also showed unchanged and S+E increased maximum EMG after 24 weeks during maximal isometric muscle actions. A high correlation (p<0.001, r=0.83) between the individual changes in voluntary activation and maximal knee extension force was found for E+S during weeks 13–24. Neural adaptations showed indications of being compromised and highly individual relating to changes in isometric strength when E+S-training was performed, while gains in one-repetition maximum, endurance performance and hypertrophy did not differ between the training modes.
Keywords: concurrent training; order effect; voluntary activation